The Impact of EPS, DER, and ROE on Firm Value for IDX-Listed Property and Real Estate Companies (2017-2021) - Agus (Jurnal Indonesia Sosial Sains, 2025)
The purpose of this study is to determine the effect of Earning Per Share (EPS), Debt to Equity Ratio (DER) and Return on Equity (ROE) on Company Value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This type of research is classified as quantitative research. The study used a simple random sampling method and was obtained by 6 companies. The data analysis methods used in this study are descriptive statistical analysis, classical assumption test and multiple linear regression analysis. The results of this study show that partially Earning Per Share (EPS) has a negative and significant effect on Company Value, Debt to Equity Ratio (DER) has a significant positive effect on Company Value and Return on Equity (ROE) has a positive and significant effect on Company Value. Then simultaneously the variables Earning Per Share (EPS), Debt to Equity Ratio (DER) and Return on Equity (ROE) have a positive and significant effect on the Company's Value with a Calculated value of 21.031 greater than Ftable 2.98 (21.031 > 2.98) with a significance value smaller than 0.001 < 0.05. So it can be concluded that Ho was rejected and Ha was accepted. And the value of the determination coefficient (adjusted R2) of 0.584 shows that the variables Earning Per Share (EPS), Debt to Equity Ratio (DER) and Return on Equity (ROE) have an influence of 67.4%. While the remaining 32.6% were influenced by other variables outside this study.